Burkholderia cepacia cervical spondylodiscitis in a 39-year-old immunocompetent woman after a rhinoplasty: A case report and review of literature - Perona-Fajardo, Francisco (2024)
Background: Burkholderia cepacia has been described as a rare etiology for spondylodiscitis (SD) after surgical procedures. Case Description: We report a rare case of cervical SD caused by B. cepacia in a 39-year-old immunocompetent woman after a rhinoplasty treated with complex cervical surgery and prolonged antibiotic therapy. The follow-up visits showed no recurrence of symptoms. Conclusion: Diagnostic and therapeutic of rare spinal infections, particularly those caused by atypical pathogens such as B. cepacia, are challenging. Identification and personalized therapy are crucial.